In vitro rooting and hardening of clonal cherry rootstock Gisela 5 (Prunus cerasus × Prunus canescens) - KUMAR, AKHIL; SHARMA, VISHAL; THAKUR, MANISHA (The Indian Journal of Agricultural Sciences, 2020)
A technique for in vitro rooting and hardening of Gisela 5 (Prunus cerasus x Prunus canescens) cherry rootstock has been developed. In vitro shoot cultures maintained by routine subculturing were used as source of microshoots for rooting experiments. In single step rooting procedure, maximum rooting (100%) was achieved on full strength MS medium fortified with 0.5 mg/l IBA with thin, long roots devoid of callus. In two step procedure of rooting, maximum rooting (60.00%) was observed after 24 hours dark incubation in half strength MS broth fortified with 0.1 and 0.4 mg/l IBA, followed by transfer to semisolid half strength MS basal medium. Addition of activated charcoal (0.4%) in half strength MS medium fortified with 0.5 mg/l IBA showed 40.06% rooting without callus, whereas in phloroglucinol (0.1%) supplemented medium only callus was observed at the bases of the shoots which did not lead to root formation. The in vitro rooted plantlets were successfully hardened in sand: soil: FYM (1:1:1) with 100 per cent survival in the month of August. After two months these plants were transferred to bigger pots containing sand: soil: FYM (1:1:1) and are showing normal growth without any morphological variations.